Designing collaborative learning wizard to assist instructors in utilizing tools in LMS - Mastura, Mohd Azlim; Kalthom, Husain; Burairah, Hussin; Zulisman, Maksom (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2016)
Learning Management System (LMS) offers lots of advantages; however it demands lots of responsibilities from instructors and students. Past researchers addressed that one of the barriers in implementing LMS in learning and teaching practices is lack of instructors' knowledge and motivation to utilize LMS in their teaching and practices. This study was conducted to design an assisted pedagogical agent named Collaborative Learning Wizard (CLW). CLW is to assist instructors to design collaborative learning activities by utilizing the tools found in LMS. Before designing the CL W, a survey was conducted to explore the utilization of tools in learning management system (LMS) among instructors in their learning and teaching practices in a public university. The results reveal that even though instructors have a positive perception towards the LMS utilization, however their level of utilization is low. The results also show that instructors do not have sufficient time to explore the available tools in LMS in order to utilize them in the appropriate ways. Thus, this study proposed a CL W which aims to facilitate instructors in utilizing the tools found in the LMS. The wizard provides guidance for instructors in the construction of learning activities using the existing tools found in LMS. Thus, LMS tools can be utilized optimally and students' performance will be enhanced at the same time.